Remo Williams : the adventure begins ... [videorecording (Blu-Ray)] - Wood, Christopher, 1935-2015; Ward, Fred, 1942-2022; Pataki, Michael, 1938-2010; Brimley, Wilford, 1934-2020; Mulgrew, Kate, 1955-; Murphy, Warren (Kino Lorber, 2022)
When a street-smart NYPD cop regains consciousness after a bizarre mugging, he has a new face and a new identity! Now he's Remo Williams, the number one recruit of a top-secret organization, and he's toppling evil at every turn, even atop the Statue of Liberty, in this '80s action-comedy classic. Trained by a quirky martial arts master to dodge bullets, brave terrifying heights and thwart attackers with his bare hands, Remo becomes the ultimate criminal exterminator. But when he faces off against a corrupt millionaire and his army of henchmen, the real adventure begins!